Vowel Length in Kasim, Samoma and Birifor - Issoufou François TIROGO & Noéllie SOUBEIGA (Akofena, 2023)
Abstract: In a comparative approach, this article reports on the status of vowel length in Kasim, Samoma and Birifor. The purpose of this study is to highlight the similarities and differences that exist between these three languages regarding vowel quantity. Using a qualitative approach, the analysis was based on a corpus drawn largely from data from Bonvini (1974), Kedrebeogo (1989) and Tirogo (2018). Following the theory developed by Prieto (1954), the study reveals that vowel length in these three languages has no phonemic status. It receives a biphonematic interpretation. The vowel quantity is a combinatorial fact. It is a relevant contrastive and not oppositional trait. Based on observed facts, the CVV sequence in all three languages has two syllables. Each of the vowels in this sequence constitutes the nucleus of a syllable, the second having an empty attack.